Electrical Properties of Horizontal Array Capacitor Using Composite Organic Dielectric Layer of Impregnated Glass-Fiber Epoxy - Hwa-Sun Park; Young-Il Na; Sang-Min Lee; Su-Jeong Suh; Yong-Soo Oh; Joon-kyun Lee; Sang Gweon Kim; Sang-Woo Han; Ho-Young Cha; Jung-Rag Yoon (Advances in Polymer Technology)
We introduce a horizontal array capacitor with nine capacitances in a single body using an organic dielectric layer impregnated with glass fiber as a prepreg sheet. An organic solid horizontal array capacitor with a dielectric of prepreg materials of the epoxy type can implement the nine capacitances in a single body via a unique simple lamination and cutting process. We then investigate the basic electrical properties of a horizontal array capacitor. The organic solid array capacitors with five electrodes and four dielectrics are Cu/PPG layer/Cu/PPG layer/Cu/PPG layer/Cu/PPG layer/Cu with a horizontal array structure. The size of a completed array capacitor is 2.85 × 2.85 mm. The height of the fabricated array capacitor in the vertical direction is 0.5 mm, with nine capacitances possessing a series-type structure. The average capacitance value of C1, C2, C3, and C4 is 1.98 nF, and each tolerance has a value within 1% based on the average value. The temperature change rate in the capacitance maintains a nearly linear characteristic, but the rate of change tends to increase finely from 120°C or more. The capacitance values of C5, C6, and C7 with the parallel circuit were measured according to the voltage. Impedance and ESR (equivalent series resistor) of C1 were measured according to frequency and temperature.